2016
DOI: 10.1080/00343404.2015.1133904
|View full text |Cite
|
Sign up to set email alerts
|

A gravity model of remittance determinants: evidence from Latin America and the Caribbean

Abstract: Given the importance of remittances it is crucial for the governments and the financial sectors in the region to recognize the specificity of each kind of remittance. A systematic analysis of the determinants of remittances would provide invaluable insights to policy makers and contribute to the design of more appropriate regulations. This in turn can promote an effective strategy for the mobilisation of remittances. In this paper the macroeconomic determinants of remittances are estimated for a set of Latin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
2
11
1
2
Order By: Relevance
“…We focus on the effect of remittances on financial development, taking into account the level of remittances to differentiate the panel. However, it is possible to refer to the literature on the determinants of remittances to assess the feedback effect (see, e.g., Adams, ), Singh, Haacker, Lee, & Le Goff, ; McCracken, Ramlogan‐Dobson, & Stack, ).…”
Section: Resultsmentioning
confidence: 99%
“…We focus on the effect of remittances on financial development, taking into account the level of remittances to differentiate the panel. However, it is possible to refer to the literature on the determinants of remittances to assess the feedback effect (see, e.g., Adams, ), Singh, Haacker, Lee, & Le Goff, ; McCracken, Ramlogan‐Dobson, & Stack, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is common for gravity models to use border indicators and geographic distance as proxies for remittance costs (Lueth and Ruiz-Arranz, 2008;Frankel, 2011;McCracken et al, 2017). We find that remittance amounts are more than 50 percent higher for households who have at least one member who was born in Mexico.…”
Section: Distance and Geographic Factorsmentioning
confidence: 84%
“…So, they are unwilling to invest in their home country and send less money. Bettin, Presbitero, and Spatafora (2014) and McCracken et al (2017) have found that migrants are motivated by altruism and self‐interest. Schiopu and Siegfried (2006) used a panel of 21 countries in their analysis and have found that altruism has a significantly positive effect on remittances, and migrants are unmotivated by investments.…”
Section: Literature Review: Determinants Of Workers’ Remittances and mentioning
confidence: 99%